Comparing Organizational Configurations of Principal Autonomy in Finland and New York - Leonardatos, Harry (State University of New York at Albany, 2015)
This exploratory study compares organizational configurations of principal autonomy in Finland and New York State. Evidence from Finnish school site visits and surveys distributed to principals in New York State and Finland is utilized to compare principal autonomy in two distinct educational settings. The distinguishing feature of the U.S. school system is local control by school boards, which dates back to the colonial era (Wong & Langevin, 2005). This organizational setting contrasts from the educational system in Finland where the central government still holds statutory responsibility for education, but has decided to delegate decisions affecting the daily processes of a school to the principal and staff of each individual schools (Caldwell & Harris, 2006; Sabel, Saxenian, Miettinen, Kristensen, & Hautamäki, 2010). Finland was chosen for this study because of its recent success on PISA and the attention Finland has received from U.S. policymakers, reformers, professors, and the media. If the Finnish school system is a “miracle” as some proclaim (Darling-Hammond, 2010), then what can we learn from this organizational setting? The hypothesis of this study is that principals in devolved and radically decentralized settings (e.g. New York State) possess less autonomy compared to principals in settings with a distinct educational center that allows decentralized decision-making at the local level (e.g. Finland). The research questions this study proposes to consider are: 1) To what extent do principals in devolved school systems (such as New York State) exercise autonomy when making decisions compared to principals in an educational system where authority is delegated by the central government (such as Finland)? 2) Is there a relationship between principal autonomy and the type of decentralization? 3) How does the type of decentralization affect a principal’s ability to act autonomously in making decisions? To examine the validity of the hypothesis and to answer these research questions, principals from New York State and Finland were selected to answer an electronically administered survey similar to the School and Staffing Survey distributed by the U.S. Department of Education. An analysis of the survey results was utilized to help understand if a relationship exists between different organizational configurations and principal autonomy. I also went to visit schools in Finland and had the opportunity to meet with school principals and representatives of the OAJ (Trade Union of Education). Principals were asked about their autonomy in making decisions related to personnel and instruction. My findings indicate that in almost all instances, principals in Finland enjoy a higher degree of autonomy than their counterparts in New York State. Principals in New York State, which operate in an educational atmosphere where different levels of government and bureaucratic entities ratify laws, pass policies, and make decisions that affect instruction and personnel, experience a lower degree of autonomy. In contrast, principals that work in a system, such as Finland’s, where the central government delegates authority to local educational agencies and allows the administration and staff of each school to make decisions indicate a higher degree of autonomy.